Pengekalan Fonem Singkatan dan Akronim dalam Buku Makan Kapal Selam Karya Samsudin: Kajian Struktur Fonemik - Pratami, Chairunnisa; Ariyani, Farida; Sumarti; Samhati, Siti; Munaris (Universitas Muhammadiyah Kotabumi, 2025)
The aim of this study is to describe the retention of phonemes in abbreviations and acronyms in the book Makan Kapal Selam by Samsudin Adlawi. The research method used is qualitative. The data source for this study is the book Makan Kapal Selam by Samsudin Adlawi. The research data consists of sentences containing acronyms or abbreviations. Data collection techniques involve intensive reading of the book as the research object and analyzing the abbreviations and acronyms based on retaining the first, second, or third phoneme of each word. The results show there are 4 abbreviations and 5 acronyms. The abbreviations retain the first phoneme of each word, forming OK, SPBU, DPPU, and BPMIGAS. The acronyms retain the first, second, or third phoneme of each word, forming Corona, pamer paha, ketandok susu, Pertamina, and SIM. Abbreviations and acronyms with familiar phonemes tend to be accepted and understood more quickly. Therefore, the retention of certain phonemes facilitates the acceptance of these abbreviations and acronyms in society and enhances communication effectiveness.